Virological and care outcomes of community ART distribution: Experience with the PODI+ model in Kinshasa, Democratic Republic of the Congo. - Michelle M Gill; Winnie Bakebua; John Ditekemena; Cady Nyombe Gbomosa; Dieudonné Tshishi; Aimé Loando; Abhigya Giri; Roger Beni Ngantsui; Heather J Hoffman (Public Library of Science (PLoS), 2024)
Introduction Differentiated service delivery models for HIV treatment can minimize unnecessary burdens on health systems and promote efficient delivery of antiretroviral therapy (ART). Under the PODI+ (poste de distribution communautaire) model, ART multi-month dispensation (MMD) was provided by lay workers (peers) in communities. We compared outcomes among clinically stable adults living with HIV receiving MMD via PODI+ or health facility (HF). Methods Clients receiving MMD at nine HFs and two PODI+ sites in Kinshasa were followed prospectively for one year (2018-2020). Medication possession ratio (MPR) was measured as proportion of total days with medication during the study through record abstraction at 3-month intervals. Viral load was assessed at enrollment and 12 months. We compared MPR and viral load suppression by arm and examined associations and potential confounders using unadjusted and adjusted odds ratios (AOR). Likert-style client satisfaction was collected during 12-month interviews and described by arm. Results Odds of maintaining viral load suppression at 12 months for PODI+ participants were two times that for HF participants. In adjusted models, PODI+ participants had 1.89 times the odds of being suppressed at 12 months compared to HF participants (95% CI: 1.10, 3.27). No significant differences in MPR were found between groups (OR: 0.86, 0.38-1.99). Older participants had significantly higher odds of MPR (AOR: 1.02, 95% CI: 1.01, 1.03) and viral suppression (AOR: 1.03, 95% CI: 1.00, 1.07). Satisfaction with services was ≥87% overall, but PODI+ participants rated time spent at site, provider attributes and other care aspects more favorably. Conclusions Participants receiving MMD via peer-run community distribution points had similar MPR, but better virological outcomes and greater satisfaction with care than clinically similar participants receiving MMD through facilities. PODI+ could be a useful model for expansion to serve larger clinic populations from overburdened health facilities, particularly as policy shifts towards more inclusive MMD eligibility requirements.